Incidental historiographic faux pas of venous air embolism in laparoscopy, reviewed critically: humanum est errare - Kumar, Shiv; Sudrania, Om P. (International Surgery Journal, 2018)
Historiographic antecedents about ambient air (AA) for embolism in operative laparoscopy (OL) are critically reviewed to decipher its representation; for its immense clinical and economic implications. Rumours of air embolism (AE) in beginning of twentieth century were based on rampant use of air tamponade in abdomen and chest for tuberculosis in absence of definitive treatment. News of AE in head, neck, dental and other open surgeries also compounded negative image of air for embolism. Resultant antiair heresy continued in medical press globally bereft of actual knowledge of etiopathophysiology of AE or gas embolism and biomechanics of pneumoperitoneum (PP). This incidental blemish was extended to OL also with divergent etiopathophysiology even when gas used was or is other than air, e.g., CO2, N2O, or O2, etc in PP and none of them are similar to each other in physical or chemical characters.